2007
DOI: 10.1111/j.1439-0531.2006.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sperm Cryopreservation on the European Eel Sperm Viability and Spermatozoa Morphology

Abstract: The main objective of the present work was to study the effect of cryopreservation of European eel sperm both on the sperm viability and the spermatozoa head morphology. Spermatozoa morphology was evaluated with computer-assisted morphology analysis after collection in fresh samples, after adding the freezing medium containing dimethyl sulfoxide as cryoprotectant and, finally, after the cryopreservation process and thawing. Cell viability was assessed, in both fresh and thawed samples, by Hoechst 33258 stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 36 publications
1
34
0
3
Order By: Relevance
“…Former studies have shown that hCG could induce spermatogenesis and sperm maturation in the European eel [4,[19][20][21][22][23]. This treatment promotes a plasma increase of androgen (11-ketotestosterone ) by the Leydig cells [13,15,16,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Former studies have shown that hCG could induce spermatogenesis and sperm maturation in the European eel [4,[19][20][21][22][23]. This treatment promotes a plasma increase of androgen (11-ketotestosterone ) by the Leydig cells [13,15,16,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Relación entre valores porcentuales de motilidad espermática y fecundación. motilidad espermática post congelación-descongelación de 75,1 ± 1,7% (Marco-Jiménez et al, 2006;Asturiano et al, 2007), o en Sparus aurata donde se obtuvieron motilidades de 70,0 ± 4,7% usando una solución crioprotectora formada por DMSO y albúmina sérica de bovino (BSA) (Cabrita et al, 2005). Estos resultados sugieren que la inclusión de vitelo de huevo de gallina (VHG) dentro de la solución crioprotectora que se utilizó en el proceso de criopreservación de los espermatozoides de P. adspersus, generaría una mayor protección durante el proceso de congelación que sería proporcionada por las lipoproteínas presentes en el VHG y estar previniendo de daños en la membrana plasmática (Scott & Baynes, 1980;Suquet et al, 2000) o incrementando la resistencia de la membrana celular ante el estrés osmótico durante el congelamientodescongelamiento de los espermatozoides (Cabrita et al, 1998).…”
Section: Discussionunclassified
“…These sperm biomarkers have so far been documented in scientific papers, and several traits of the fish/sperm itself, such as osmolality, pH and chemical composition of the seminal plasma Asturiano et al, 2007;Sadiqul and Akhter, 2011) have been linked to the ability of sperm to fertilize the ova. Some of these parameters can be scored relatively easily and are commonly used because no expensive equipment is needed and they are quick and easy to assess.…”
Section: Basic Parameters For Assessing Sperm Qualitymentioning
confidence: 99%
“…These sperm biomarkers have so far been documented in scientific papers, and several traits of the fish/sperm itself, such as osmolality, pH and chemical composition of the seminal plasma (Asturiano et al, 2005;Ciereszko, 2008); enzymatic activity (Burness et al, 2005); ATP concentration (Suquet el al., 2010); spermatocrit and sperm density (Harald et al, 2001;Sørensen et al, 2013); sperm motility (Ottesen et al, 2009); or sperm morphology and ultrastructure Asturiano et al, 2007;Sadiqul and Akhter, 2011) have been linked to the ability of sperm to fertilize the ova. Some of these parameters can be scored relatively easily and are commonly used because no expensive equipment is needed and they are quick and easy to assess.…”
Section: Basic Parameters For Assessing Sperm Qualitymentioning
confidence: 99%
See 1 more Smart Citation